Impact of magnetic fields on the early ontogeny of the jaguar cichlid Parachromis managuensis Günther, 1867 and the green terror Andinoacara rivulatus Günther, 1860 - R. Piesiewicz; J. Krzystolik; K. Formicki (The European Zoological Journal)
The study examined the impact of magnetic fields with intensities of 1 mT, 3 mT, and 5 mT on two species of cichlid fish (family Cichlidae), focusing on the rate of embryogenesis, changes in embryonic heart function, and egg survival rates. Magnetic fields influenced the eggs of the jaguar cichlid, particularly those exposed to magnetic fields of 1 mT and 3 mT, by accelerating development and improving survival rates. The shortest embryogenesis time in the green terror was observed in the control group (without a generated magnetic field) and in trial 3 (5 mT). In general, our findings provide important insights into the effects of magnetic fields on cichlid fish, which could lead to improved breeding outcomes and better conservation of these species in their natural habitats.